السياحة والتغير الاجتماعي في تونس: دراسة استطلاعية وتحليلية في الآثار الاجتماعية والثقافية لتطور قطاع السياحة بالجنوب الشرقي - بن عمر, حافظ (كلية العلوم الإنسانية والاجتماعية, 2003)
Keywords: Tourisme – Djerba

العلامة أبو المؤثر الصلت بن خميس الخروصي حياته وآثاره - الوهيبي, عمر بن حمد بن سليمان (كلية العلوم الشرعية, 2003)

برد اليقين في تخريج أحاديث سيد المرسلين من مدونة أبي غانم الخراساني بترتيب القطب - الرواحي, محمد بن حمود بن حمد (كلية العلوم الشرعية, 2003)

الحركة اليوسفية بجهة صفاقس 1955 - 1956 - الزواري, محمد (كلية الآداب والعلوم الإنسانية, 2003)
Keywords: Ben Youssef; Salah 1907-1961

منهج الجناوني ( ق 5-6هـ ) من خلال كتابة الوضع - الحارثي, سلطان بن محمد (جامعة الزيتونة, 2003)
Keywords: Jannāwunī; Yaḥyā b. al-Khayr

تحقيق مشكاة الأصول للشيخ العلامة حمد بن عبيد السليمي - الرحبي, عامر بن خليفة (كلية العلوم الشرعية, 2003)
Edition: الطبعة الأولى

الشيخ عمروس و منهجه الفقهي و العقائدي من خلال كتاب أصول الدينونة الصافية - السعدي, مهنا بن راشد (كلية العلوم الشرعية, 2003)
Edition: الطبعة الأولى

الجوانب الموسيقية بالعرس التقليدي بمطماطة - الحمروني, حنان (المعهد العالى للموسيقى, 2003)
Keywords: Coutumes – Matmata

الأغنية الشعبية غمراسن نموذجا - القاسمي, فتحية (المعهد العالى للموسيقى, 2003)
Keywords: Musique – Ghomrassen

‎⁨وظيفة التراث الديني في شعر مفدي زكرياء - حجاب, عبد اللطيف (جامعة الجزائر, 2003)
Keywords: Poésie – Mzab

Une génération de militants de l'école primaire à l'université : le cas de l'AEEM (l'association des élèves et étudiants du Mali) - Djiré, Salif Mandela (Université Paris 8, 2003)

Parcours moderne d'une pratique ancestrale : de la marginalité à la banalisation du magnétisme curatif - Philippe, Stéphanie (Université Paris 8, 2003)

Coutumes, modes de vie et économie de transhumance des Peuls de Massina - Bathily, Aboubacar Idrissa (Université Paris 8, 2003)

Les groupements coutumiers ou classes d'âge à la Grande Comore - Barwane, Ibrahim (Université Paris 8, 2003)
Keywords: Moeurs et coutumes – Comores

Le Palo-Monte à Cuba - Kerestetzi, Katerina (Université Paris 8, 2003)

Entwicklung eines Internet-Geoinformations für archäologische Fundstätten am Beispiel der omanischen Oase Ibra' - Grosch, Martin (Technischen Fachhochschule Berlin, 2003)
Keywords: Archéologie – Oman

Etudes d'anthropologie historique et culturelle sur le M'zab - Cherifi, Brahim (Université Paris 8, 2003)

La Scuola Per L’impero Politiche Educative Per Gli Arabi Di Libia in Epoca Fascista (1922-1940) - Pasquale, Francesca Di (Università degli Studi di Pisa, 2003)
Keywords: Linguistique – Djebel Nefousa

دولة مدرار "الصفرية" بالمغرب الأقصى الإسلامي دراسة تاريخية حضارية 140-347هـ/707-908م - برناوى, وفاء يعقوب جبريل (جامعة أم القرى, 2003)

Oman through British eyes : British travel writing on Oman from 1800 to 1970 - Hajri, Hilal al- (University of Warwick, 2003)
This thesis focuses on the images of Oman in British travel writing from 1800 to 1970. In texts that vary from travel accounts to sailors’ memoirs, complete travelogues, autobiographies, and letters, it looks at British representations of Oman as a place, people, and culture. It argues that these writings are heterogeneous and discontinuous throughout the periods under consideration. Offering diverse voices from British travellers, this thesis challenges Edward Said’s project in Orientalism (1978) which looks to Western discourse on the Middle East homogenisingly as Eurocentric and hostile. Chapter one explores and discusses the current Orientalist debate suggesting alternatives to the dilemma of Orientalism and providing a framework for the arguments in the ensuing chapters. Chapter two outlines the historical Omani-British relations, and examines the travel accounts and memoirs written by several British merchants and sailors who stopped in Muscat and other Omani coastal cities during their route from Britain to India and vice versa in the nineteenth century. Chapter three is concerned with the works of travellers who penetrated the Interior of Oman. James Wellsted’s Travels in Arabia (1838), Samuel Miles’ The Countries and Tribes of the Persian Gulf (1919) and other uncollected travel accounts, and Bertram Thomas’s Alarms and Excursions (1932) are investigated in this chapter. Chapter four considers the travellers who explored Dhofar in the southern Oman and the Ruba Al-Khali or the Empty Quarter. Precisely, it is devoted to Bertram Thomas’s Arabia Felix (1932) and Wilfred Thesiger’s Arabian Sands (1959). Chapter five looks at the last generation of British travellers who were in Oman from 1950 to 1970 employed either by oil companies or the Sultan Said bin Taimur. It explores Edward Henderson’s Arabian Destiny (1988), David Gwynne-James’s Letters from Oman (2001), and Ian Skeet’s Muscat and Oman (1974). This thesis concludes with final remarks on British travel writing on Oman and recommendations for future studies related to the subject. The gap of knowledge that this thesis undertakes to fill is that most of the texts under discussion have not been studied in any context.
Keywords: Récits de voyage – Oman

Oman and the Islamic caliphate 11-447/632-1055 : the military struggle - Alawi, Badar Hilal Khalifa al- (University of Manchester, 2003)

حدث انفجار معبد الغربية بجربة 11أفريل 2002 من خلال الصحف اليومية التونسية , الصباح , الصحافة , الحرية :مثالا - البلطي, محمد (معهد الصحافة وعلوم الإخبار, 2003)

الشيخ أطفيش ومنهجه في التفسير (1236 هـ - 1332 هـ) - السرحني, يوسف بن إبراهيم بن سعيد (جامعة الزيتونة, 2003)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Coran – Commentaires – 19e siècle

أحكام المفقود في المذهبين المالكي والإباضي وقانون الأحوال الشخصية العماني: دراسة مقارنة - البوسعيدي, إسحاق بن أحمد بن ناصر (جامعة الزيتونة, 2003)

Unité de production textile entre Artisanat et Industrie à Houmt-Souk Djerba - Ben Younes, Rym (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2003)
Keywords: Artisanat – Djerba

Conception d’un ouvrage sur la route Djerba Zarzis - Daoud, Wissem (Ecole Nationale d'Ingénieurs de Tunis, 2003)
Keywords: Urbanisme – Djerba

Regard vers le ciel : Un planétarium observatoire à l’île de Djerba - Ben Hmidane, Boubaker (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2003)
Keywords: Architecture – Djerba

Centre d’accueil et de Recherche en Architecture Djerbienne - Jdaa, Kilani (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2003)
Keywords: Architecture – Djerba

Vers la conception d’une Unité de production cinématographique à Djerba - Mabrouk, Selim (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2003)
Keywords: Architecture – Djerba

Un Musée du Patrimoine marin Djerbien - Ouderni, Leila (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2003)
Keywords: Architecture – Djerba

Etude d’aménagement de subkhet Lella Hadhria à Djerba - Rezgui, Atef (Ecole Nationale d'Ingénieurs de Tunis, 2003)
Keywords: Architecture – Djerba

An Outline of the Shilha (Berber) Vernacular of Douiret (Souther Tunisia) - Gabsi, Zouhir (University of Western Sidney, 2003)
Keywords: Linguistique

Les mutations socio-spatiales culturelles et aspects anthropologiques en milieu aride, le cas de la Jeffara tuniso-libyenne (1837-1956) - Abdelkebir, Abderrahman (Université de Metz, 2003)
Keywords: Emigrations – Tribus – Jeffara

The Impact of Luxury: The Forum of Meninx, an architectural investigation - Morton, Thomas (University of Pennsylvania, 2003)
Keywords: Archéologie – Djerba